2022
DOI: 10.1161/jaha.121.023524
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Door‐to‐Needle Time for Intravenous Thrombolysis Is Safer and Improves Outcome in the Czech Republic: Nationwide Study 2004 to 2019

Abstract: Background The benefit of intravenous thrombolysis is time dependent. It remains unclear, however, whether dramatic shortening of door‐to‐needle time (DNT) among different types of hospitals nationwide does not compromise safety and still improves outcome. Methods and Results Multifaceted intervention to shorten DNT was introduced at a national level, and prospectively collected data from a registry between 2004 and 2019 were analyzed. Generalized estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…There were no safety concerns related to shortened logistics: stroke centres that passed simulation training tended to have less intracerebral parenchymal haematomas (5.4% vs 3.5%, p=0.054). This is consistent with our other findings which demonstrated that longer DNT was associated with more intracerebral bleedings 15 16…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were no safety concerns related to shortened logistics: stroke centres that passed simulation training tended to have less intracerebral parenchymal haematomas (5.4% vs 3.5%, p=0.054). This is consistent with our other findings which demonstrated that longer DNT was associated with more intracerebral bleedings 15 16…”
Section: Discussionsupporting
confidence: 93%
“…However, our study documents that stroke centres after simulation training had shorter DNT, and our other studies documented that such shortening improves patient outcomes. 16 The strengths of our study are the presence of a control group, a nationwide character with a large number of patients involved, documented safety, and a reliable and prospective collection of outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Using other supplementary activities such as simulation training and with involvement of Angels Initiative, national DNT time for intravenous thrombolysis was shortened to national median of 25 minutes in 2018 45 and 22 minutes in 2019. 46 Next, analysis of impact of shortening of DNT on outcome documented that dramatic shortening of DNT improved outcome without any negative impact on eg risk of bleeding (actually it was opposite=less bleeding). 46 Based on the evidence, that ultrashort DNT is feasible to be achieved in any type of the hospital and that such shortening is improving outcome, Czech Stroke Society modified national stroke guidelines and since 2021 recommend that target median DNT time should be below 20 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…A shorter DNT time not only increased the odds of achieving a modified Rankin score 0 to 1 on day 90, as it also decreased the odds of parenchymal ICH, mortality 9 and even long-term recurrences of stroke. 10 For those patients who could be treated in their first hour of evolution, the odds of satisfactory clinical outcome at 3 months almost doubled.…”
Section: Discussionmentioning
confidence: 96%
“…Guidelines recommend that IVT should be administered with short DTN time, as patients experiencing a large vessel AIS can lose 1.9 million neurons, 14 billion synapses, and 12 km of myelinated fibers every minute. 8 A shorter DNT time not only increased the odds of achieving a modified Rankin score 0 to 1 on day 90, as it also decreased the odds of parenchymal ICH, mortality 9 and even long-term recurrences of stroke. 10 For those patients who could be treated in their first hour of evolution, the odds of satisfactory clinical outcome at 3 months almost doubled.…”
Section: Discussionmentioning
confidence: 99%